1971
DOI: 10.1111/j.1748-1716.1971.tb04877.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Dynamics of Ventilation and Heart Rate with Step Changes in Work Load from Different Load Levels

Abstract: Broman, Svetlana and O. Wigertz, Transient dynamics of ventilation and heart rate with step changes in work load from different load levels. Acta physiol. scand. 1971. 81. 54–74.Transient dynamics of ventilation (V̇) and heart rate (HR) in response to 650 kpm/min step changes in work load were analyzed in six male athletes performing submaximal cycling exercise in the supine position, with the steps initiated at different levels of stable‐state exercise, including “loadless” pedaling (0 kpm/min). By applying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
20
0
3

Year Published

1982
1982
2000
2000

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 16 publications
4
20
0
3
Order By: Relevance
“…The exponential hyperbolic sine function is useful for the quantitative evaluation of the HR responses to different constant loads. The HR trends in response to three different loads observed in the present study were in agreement with those in previously reported studies [5][6][7][8][9][10], and HR trends can thus be analyzed and discussed. The findings of the successful fitting of the exponential hyperbolic sine curve to the HR changes in response to lowload exercise indicated that the HR response includes an oscillation component (i.e., an inductor component).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The exponential hyperbolic sine function is useful for the quantitative evaluation of the HR responses to different constant loads. The HR trends in response to three different loads observed in the present study were in agreement with those in previously reported studies [5][6][7][8][9][10], and HR trends can thus be analyzed and discussed. The findings of the successful fitting of the exponential hyperbolic sine curve to the HR changes in response to lowload exercise indicated that the HR response includes an oscillation component (i.e., an inductor component).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the relation of each coefficient to physiological indices such as sympathetic tone, etc. could not be determined, as was also the case in the previous fittings [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations